Effect of sex, age and final live mass on carcass traits of fattening dairy cattle - Moomak, P.; Tuntivisoottikul, K. (International Journal of Agricultural Technology, 2020)
Most animals (63.25 %) obtained a marbling score of 2 while 19.27 % obtained a score of 1. Marbling score was not affected by all the studied factors (P>0.05). Sex had a significantly stronger effect on hot and chilled carcass mass (P<0.01): averages for both hot and chilled carcass masses of males were greater than those of females. All studied traits (P<0.05), except chilling loss (P>0.05), were influenced by age. Averages of both hot and chilled carcass mass, both in kg and in proportion of animals with 3 yrs age were higher, but not statistically different from those of 4 yrs animals. Most traits were significantly affected by final live mass (P<0.01). As the final live mass increased, both hot and chilled carcass mass in kg and as a fraction increased, and chilling loss both in kg and as a fraction decreased.